Charge storage mechanisms of a π–d conjugated polymer for advanced alkali-ion battery anodes. Issue 27 (29th June 2022) - Kapaev, Roman R.; Zhugayevych, Andriy; Ryazantsev, Sergey V.; Aksyonov, Dmitry A.; Novichkov, Daniil; Matveev, Petr I.; Stevenson, Keith J.
Abstract : Charge storage mechanisms of NiBTA, a 1D π–d conjugated polymer derived from benzenetetramine, are studied in Li-, Na- and K-based batteries with a set of advanced experimental and computational methods. Abstract : The demand for fast-charging metal-ion batteries underlines the importance of anodes that work at high currents with no risk of dendrite formation. NiBTA, a one-dimensional Ni-based polymer derived from benzenetetramine (BTA), is a recently proposed promising material for safe fast-charging batteries. However, its charge–discharge mechanisms remained unclear and controversial. Here we solve the controversies by providing the first rigorous study using a combination of advanced theoretical and experimental techniques, including operando and ex situ X-ray diffraction, operando Raman spectroscopy and ex situ X-ray absorption near-edge spectroscopy (XANES). In safe potential ranges (0.5–2.0 V vs. M + /M, M = Li, Na or K), NiBTA offers high capacities, fast charge–discharge kinetics, high cycling stability and compatibility with various cations (Li +, Na +, K + ). In the Na- and K-based cells, fast bulk faradaic processes are manifested for partially reduced states. Atomistic simulations explain the fast kinetics by facile rotations and displacements of the macromolecules in the crystal, opening channels for fast ion insertion. The material undergoes distinct crystal structure rearrangements in the Li-, Na- and K-based systems, which explains different electrochemical features. At the molecular level, the charge storage mechanism involves reversible two-electron reduction of the repeating units accompanied by a change of the absorption bandgap. The reversible reduction involves filling of the orbitals localized at the ligand moieties. No reduction of NiBTA beyond two electrons per repeating unit is observed at potentials down to 0 V vs. M + /M.